Development and validation of a scale to measure caregiver skills in eating disorders. Issue 3 (29th October 2014) - Hibbs, Rebecca; Rhind, Charlotte; Salerno, Laura; Lo Coco, Gianluca; Goddard, Elizabeth; Schmidt, Ulrike; Micali, Nadia; Gowers, Simon; Beecham, Jennifer; Macdonald, Pamela; Todd, Gillian; Campbell, Iain; et al.
ABSTRACT: Objective: The aim of this study was to develop and validate a new questionnaire designed to measure caregiver skills that, in line with the interpersonal component of the cognitive interpersonal maintenance model (Schmidt and Treasure, J Br J Clin Psychol, 45, 343–366, 2006), may be helpful in the support of people with anorexia nervosa (AN). A further aim is to assess whether this scale is sensitive to change following skills‐based caregiver interventions. Method: The Caregiver Skills (CASK) scale was developed by a group of clinicians and caregivers. Preliminary versions of the scale devised for both caregivers and parents were given at baseline and at follow‐up after two studies of caregiver interventions (a clinical trial of the effectiveness of guided self‐help and training workshops). Exploratory and confirmatory factor analyses (CFA) were used to test the factorial structure of the CASK scale. Cronbach's alpha was used to measure internal consistency of the CASK scales. Results: Exploratory Factor Analysis suggested a six component solution ( Bigger Picture, Self‐Care, Biting‐Your‐Tongue, Insight and Acceptance, Emotional Intelligence and Frustration Tolerance ) and this model was confirmed with CFA. Significant clinically relevant correlations were found between the CASK scales and other standardised measures of caregivers' attitudes and behaviours. Furthermore, greater improvements on abilities measured by the CASK scale were found in caregivers who received skills‐training than caregivers assigned to a 'treatment as usual' condition. Discussion: The CASK scale is a measure of the fidelity of interventions based on the cognitive interpersonal maintenance model and is sensitive to the intensity of the intervention provided. © 2014 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:290–297)